CORN COB AND COCOA SHELL WASTE: A RENEWABLE ENERGY SOURCE SOLUTION - Susilo, Gunawan Budi; Hayati, Nur (Department of Mechanical Engineering Education, 2025)
This study aims to assess the potential of corn cob and cocoa shell waste as a renewable energy source and develop effective technology to convert these wastes into renewable energy, as well as test the efficiency and safety of using alternative fuels produced from corn cob and cocoa shell waste. The stages of this research start from the stage of making briquettes and testing the physical briquettes and water boiling tests. The results showed that corn cob and cocoa shell waste can be converted into biomass that can be used as an energy source. The charcoal briquettes produced from corn cob waste and cocoa peels have a high calorific value, so they can be used as an effective energy source. In addition, the use of corn cob and cocoa shell waste as an energy source can reduce the amount of waste generated and environmental pollution caused by burning waste. Corn cobs and cocoa pods have good thermal properties to be used as biomass fuel in renewable energy generation systems. The study evaluated the physical quality based on variation of corn cobs and cocoa shells mixture composition. The physical quality to be analyzed were stability, density, thermal properties, and heat of combustion. With the right process, these two wastes can be a solution for environmentally friendly energy needs, while providing economic benefits for farmers. Proper management of these wastes can accelerate the shift towards renewable energy, reduce waste and mitigate negative environmental impacts.